Building Green Trust: How Eco-Friendly Advertising Shapes Beauty Consumption in Indonesia - Sania Nuraziza; Eva Yuniarti Utami; Agus Suaidi Hasan (Sharia Business Management UIN Raden Intan Lampung, 2026)
The study analyzes the influence of green advertising on green purchasing behaviors through the mediating effect of green trust. The empirical research employs a quantitative research method where the data was collected through a questionnaire administered to 120 eco-conscious consumers of local beauty products via purposive sampling. The collected data was analyzed using PLS-SEM. The empirical findings indicate that green advertising positively influences green trust and green purchase decisions. Moreover, green trust positively influences green purchasing decisions and serves as a complementary partial mediator that significantly increases the indirect influence of green advertising on purchasing decisions. The theoretical model has high explanatory power in explaining green consumer behavior in the local beauty industry. The marketing practitioners should emphasize transparency and authentic eco-messages as well as third-party certifications rather than promotional efforts in order to create green trust and overcome the issue of greenwashing skepticism. From a theoretical standpoint, the paper emphasizes green trust as the key psychological link between green communications and consumer actions in emerging markets. The main limitations of this study include the cross-sectional nature of the research design and use of self-reporting data collection. Keywords: Green Advertising, Green Trust, Green Purchase Decision, Beauty Products, Consumer Behavior.